A fast and accurate PCA based radiative transfer model: Extension to the broadband shortwave region. (April 2016) - Kopparla, Pushkar; Natraj, Vijay; Spurr, Robert; Shia, Run-Lie; Crisp, David; Yung, Yuk L.
Abstract: Accurate radiative transfer (RT) calculations are necessary for many earth–atmosphere applications, from remote sensing retrieval to climate modeling. A Principal Component Analysis (PCA)-based spectral binning method has been shown to provide an order of magnitude increase in computational speed while maintaining an overall accuracy of 0.01% (compared to line-by-line calculations) over narrow spectral bands. In this paper, we have extended the PCA method for RT calculations over the entire shortwave region of the spectrum from 0.3 to 3 microns. The region is divided into 33 spectral fields covering all major gas absorption regimes. We find that the RT performance runtimes are shorter by factors between 10 and 100, while root mean square errors are of order 0.01%. Abstract : Highlights: A fast-PCA based radiative transfer model is applied to the wavelength range 0.3–3 μm. Runtime is shorter by a factor of 10–100, accuracy of order 0.01% compared to an exact model. Model is tested for different atmospheric profiles and performance is discussed.